2017
DOI: 10.1016/j.jallcom.2016.12.406
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the body centered cubic crystal in titanium alloys by a nano-scale concentration modulation

Abstract: It is well-known that the body centered cubic (bcc) crystal in titanium alloys reaches its stability limit as the electron-to-atom (e/a) ratio of the alloy drops down to ~4.24. This critical value, however, is much higher than that of a multifunctional bcc type alloy (e/a = 4.15). Here we demonstrate that a nano-scale concentration modulation created by spinodal decomposition is what stabilizes the bcc crystal of the alloy. Aided by such a nano-scale concentration heterogeneity, unexpected properties from its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Contributed by the nano-scale Nb modulation [27], the alloy is free of the  phase, as evidenced by the in-situ SXRD profiles in Fig. 1c.…”
mentioning
confidence: 88%
“…Contributed by the nano-scale Nb modulation [27], the alloy is free of the  phase, as evidenced by the in-situ SXRD profiles in Fig. 1c.…”
mentioning
confidence: 88%
“…[115] Many previous results proved that the phase stability of Ti alloys is related to the e/a ratio. [103,116,117] The as-quenched phase constitutions of Ti alloys are reported as a function of the e/a ratio, as shown in Figure 5. [118] It shows that the stability of the β phase in Ti alloys increases with the e/a ratio.…”
Section: Design Methods For Low-modulus Ti Alloysmentioning
confidence: 99%
“…That is a key reason for low modulus. The elastic modulus of multicomponent Ti alloys [17,28,32,116,118,[122][123][124][125] against e/a ratio in Figure 7 indicates that the relationship between elastic modulus and e/a ratio in multicomponent Ti alloys is similar to binaries.…”
Section: Design Methods For Low-modulus Ti Alloysmentioning
confidence: 99%
“…In Ti-Nb binary system, the β phase separation region does not exist in the equilibrium phase diagram but it appears in the metastable phase diagram considering only the β and ω phases [14]. The spinodal decomposition in Ti-Nb-based alloys has been observed experimentally in a Ti-Nb-Ta-Zr alloy via three-dimensional atom-probe tomography [15,16]. It has been suggested that the MT behavior and mechanical properties of the alloy can be influenced by the concentration modulation of Ti and Nb introduced by the spinodal decomposition [17].…”
Section: Introductionmentioning
confidence: 98%